Chrysotimus Loew from China (Diptera: Dolichopodidae) - Wang, Mengqing; Yang, Ding; Grootaert, Patrick (Zootaxa, 2005)
The following 8 species are described as new to science: Chrysotimus acutatus Wang, Yang and Grootaert, sp. nov., C. chikuni Wang, Yang and Grootaert, sp. nov., C. guangdongensis Wang, Yang and Grootaert, sp. nov., C. ningxianus Wang, Yang and Grootaert, sp. nov., C. sanjiangyuanus Wang, Yang and Grootaert, sp. nov., C. songshanus Wang, Yang and Grootaert, sp. nov., C. xiaohuangshanus Wang, Yang and Grootaert, sp. nov., C. xuae Wang, Yang and Grootaert, sp. nov. A key to the Chinese species of the genus is presented.